The Clinical Effectiveness of Preimplantation Genetic Diagnosis for Chromosomal Translocation Carriers: A Meta-analysis - Mahdavi, Manijeh; Sharafi, Seyedeh M.; Daniali, Seyede S.; Riahi, Roya; Kheirollahi, Majid (Global Medical Genetics, 2020)
Published data on the relationship between pregnancy outcomes of preimplantation genetic diagnosis (PGD) in translocation carriers have implicated inconclusive results. To identify potentially eligible reports, an electronic search was conducted in several databases, including PubMed, Scopus, Web of Knowledge, and Cochrane. Pooled odd ratios (ORs) and 95% confidence intervals (Cis) were estimated based on a random-effect model to evaluate the strength of association between PGD and successful pregnancy outcome in translocation carriers. A total of six cohort studies were included in the current study. The meta-analysis of these studies revealed that the PGD method was associated with an increased successful pregnancy outcome of translocation carriers (OR = 8.58; 95%CI: 1.40–52.76). In subgroup analysis, there was no significant association according to the chromosomal translocation carrier origin and the type of translocated chromosomes, as well as country. In developed countries, the pregnancy outcome of PGD was significantly improved in translocation carriers (OR = 21.79; 95%CI: 1.93–245.52). The current meta-analysis demonstrated that the PGD method is associated with successful pregnancy outcome in both types of reciprocal and Robertsonian translocation carriers, especially in developed countries.
Keywords: pregnancy outcome; preimplantation genetic diagnosis; meta-analysis; translocation; recurrent miscarriage